Homology based selection of cell surface markers for the purification of goatbone marrow derived Mesenchymal Stem Cells - TYAGI, VAISHALI; FIRDAUSI, NASERA; HAKIM, BILAL AHMAD; JAIN, ANKITA; SINGH, DEEPENDRA; VYAS, AKANKSHA; MISHRA, RAJNIKANT; KUMARI, ARTI; VISHWAKARMA, ACHCHHELAL; KHARCHE, SURESH DINKAR; SACHDEV, MONIKA (The Indian Journal of Animal Sciences, 2023)
Adult stem cells are self-renewing cells and sustain for long period. Mesenchymal Stem Cells (MSCs) has been studied in a variety of species till date, however, there is limited information available for goats’ MSC surface markers. Hence, as per the developmental scenario of mammals, homology of MSCs surface markers across the species can be explored for the enrichment of goat BM-MSCs. Accordingly, in present study a pure population of goat MSCs was isolated, while using diverse antibodies against MSC surface markers from other species including human, rat and mouse. Goat bone marrow was aspirated from the iliac crest, and cultured in DMEM. Further, MSCs were enriched using human CD90 antibodies through Magnetic-Activated Cell Sorting (MACS). Once, these cells exhibited fibroblast-like morphology, the expression of stem cell markers was analysed through FACS and Immunofluorescence. Pure MSCs were observed to be highly positive for CD90 and CD29 by 98-99% and turned out to be almost negative for CD45 and CD31, while using rat antibodies, hence proving the purity of this stem cell population. These goat bone marrow-derived MSCs are used for intra-ovarian transplantation, which seems to be crucial to restoring female fertility in aged infertile goats.